Dual-virus co-infection reduces photosynthetic rate, yield, and sensitivity of photosynthetic rate to leaf-air VPD in Pseudostellaria heterophylla - Boqin Zheng; Zhenghua Wang; Lingfeng Zeng; Ding Wang; Zuyun Ye (Medicinal Plant Biology)
Viral infections exert a complex influence on plant growth, modifying tolerance to abiotic stresses, with effects varying depending on the specific virus. Pseudostellaria heterophylla, a medicinal herb, is often infected by Turnip mosaic virus and Broad bean wilt virus 2, leading to mosaic disease. This study comprehensively investigated the effects of diverse viral infections on plant growth and response to environmental factors, evaluating specific leaf weight, chlorophyll content, stomatal conductance, net photosynthetic rate, transpiration rate, yield, aqueous extract, and polysaccharide content. Results indicate that Turnip mosaic virus and Broad bean wilt virus 2 co-infection result in decreased chlorophyll content, stomatal conductance, net photosynthetic rate, transpiration rate, yield, and polysaccharide content in Pseudostellaria heterophylla, compared with Broad bean wilt virus 2 infection alone. Broad bean wilt virus 2 alone only reduces chlorophyll and polysaccharide content. Plants infected with both viruses show a reduced response to leaf-air vapor pressure deficit in stomatal conductance, net photosynthetic rate, and transpiration rate compared to singly infected plants. Thus, the eradication of Turnip mosaic virus should be prioritized for Pseudostellaria heterophylla cultivation.